"And then I found $5": Optimizing recruitment efficiency in remote clinical trials. Issue 1 (20th April 2023) - Fahey, Margaret C.; Dahne, Jennifer; Chen, Brian K.; Smith, Tracy T.; Wahlquist, Amy E.; Carpenter, Mathew J.
Abstract: Introduction: As clinical trials adopt remote methodologies, there is need to optimize efficiency of remote enrollment. Within a remote clinical trial, we aim to (1) assess if sociodemographic factors differ among those consenting via mail vs. technology-based procedures (e-consent), (2) determine if, among those consenting via mail, a small unconditional monetary reward ($5) increases likelihood of subsequent enrollment, (3) economically evaluate additional cost per additional participant enrolled with $5 reward. Methods: In the parent nationwide randomized clinical trial of adult smokers ( N = 638), participants could enroll via mail or e-consent. Logistic regression models assessed relationships between sociodemographics and enrollment via mail (vs e-consent). Mailed consent packets were randomized (1:4) to include $5 unconditional reward or not, and logistic regression modeling examined impact of reward on subsequent enrollment, allowing for a randomized study within a study. Incremental cost-effectiveness ratio analysis estimated additional cost per additional participant enrolled with $5 incentive. Results: Older age, less education, lower income, and female sex predicted enrolling via mail vs e-consent ( p < .05's). In adjusted model, older age (AOR = 1.02, p = .016) and less education (AOR = 2.23, p < .001) remained predictive of mail enrollment. The $5 incentive (vs none) increased enrollment rate by 9% (AOR = 1.64, p = .007), with estimated cost of additional $59 per additional participant enrolled. Conclusions: As e-consent methods become more common, they have potential to reach many individuals but with perhaps diminished inclusion across all sociodemographic groups. Provision of an unconditional monetary incentive is possibly a cost-effective mechanism to increase recruitment efficiency for studies employing mail-based consenting procedures.